The Seven Traps of Decentralization Policy - Fuhr, Harald (UI Scholars Hub, 2012)
Since Mid 1980s, a number of governments in developing countries initialized an ambitious decentralization policy and other policies to strengthen local governments. Nevertheless, after more or less 25 years of their implementations, the initial enthusiasm decreases. The experience in some countries shows that reform policy can trigger many new political, fiscal, and administration problems.The article shortly describes seven major problems and potential traps lurking in decentralization policy, consisting: policy trap, coordination trap, fiscal trap, debt trap, capturing trap, inequality trap, and capacity trap. The evidence presented in this article has shown that decentralization can be part of a strategy to improve the capability and effectiveness of the state. It encompasses mechanisms that increase openness and transparency, strengthen incentives forparticipation in public affairs, and where appropriate, bring government closer to the people and to the communities it is meant to serve.